INTELLECTUAL CAPITAL IN ACCOUNTING PROCESSES - Galina V. Mikhailova; Alexander S. Pavlov (Вестник Северо-Кавказского федерального университета, 2022)
The article offers a view on the typology of resources and the systemic properties of intellectual capital, the structure of intellectual capital and its relation to the outcomes and the external environment, as well as the methodology for comprehensive accounting of intellectual resources that is aimed at use of an integrated system of financial, strategic, and management accounting with transactional strategic and management accounting.